2003
DOI: 10.1292/jvms.65.745
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum Antigens Recognized by Mouse IgG at Different Stages of Infection Including Recrudescence

Abstract: ABSTRACT.Western blotting was performed to analyze Neospora caninum tachyzoite antigens recognized by mouse IgG at different stages of infection including recrudescence. At the early stage of infection, a 36-38 kDa antigen was clearly recognized by the mouse antisera. After day 48 postinoculation, the signal of the 36-38 kDa antigen gradually weakened. Meanwhile, a 43 kDa antigen was intensely and continuously recognized from 48 to 125 days postinoculation. This 43 kDa antigen was clearly detectable with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Tomioka et al . (27) stated that in an early stage of infection, a 36–38 kDa antigen was clearly recognized by mouse antisera, but the signal weakened after day 48 post‐inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tomioka et al . (27) stated that in an early stage of infection, a 36–38 kDa antigen was clearly recognized by mouse antisera, but the signal weakened after day 48 post‐inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Hemphill and Gottstein (24), Hemphill et al (25,26), and Sonda et al (15) reported that the 36 kDa antigen was a major tachyzoite surface protein. Tomioka et al (27) stated that in an early stage of infection, a 36-38 kDa antigen was clearly recognized by mouse antisera, but the signal weakened after day 48 post-inoculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation